Pengaruh Perceived Risk, Perceived Reputation, dan Trust Online terhadap Minat Beli Online Konsumen Shopee - Anisa Martiah; Heditia Umi Ismulyani; Saddam Hussein Inonu (SAFE-Network, 2023)
This study aims to analyze the influence of perceived risk, perceived reputation, and online trust on shopper's online purchase intention. The population in this study is the city of Bandar Lampung as many as 300 respondents. The sampling technique is Purposive Sampling. Data analysis using SEM (Structural Equation Model) with the PLS 3 program. The results of this study indicate that Perceived Risk has a significant positive effect on online trust, perceived reputation has a significant positive effect on online trust, online trust has a significant positive effect on purchase intention, Perceived Risk has a positive effect significant to purchase intention, Perceived reputation has a significant positive effect on purchase intention.